NbodyCP: a direct N-body simulation code for composite stellar populations of single and binary star clusters - Li, Zhongmu; Spurzem, Rainer (Research in astronomy and astrophysics, 2026)
It is well-known that some star clusters contain composite stellar populations (CSPs), in which the metallicities or (and) ages of stars are different. The formation and evolution of such clusters and their stellar populations remain unclear. Both single and binary cluster channels may lead to such CSPs. In order to simulate the formation and evolution of such CSPs in star clusters, this work develops a code of direct N-body simulation of CSPs, NbodyCP. It is applied to different clusters, in particular, to binary clusters. It shows that CSPs and different kinds of cluster pairs can be formed via dynamical processes. This will help to partially explain the formation of CSPs and various clusters. Some special cluster structures, e.g., two cores or bar-like shape, are shown to be the results of evolution of some binary clusters. The simulation also shows that the separation between the members of a binary cluster affects the time of two member clusters to combine or move away significantly.
Veröffentlicht: 26. November 2025
Gesehen am 28.01.2026